2024
DOI: 10.3389/fpsyg.2023.1339782
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence adoption in extended HR ecosystems: enablers and barriers. An abductive case research

Antarpreet Singh,
Jatin Pandey

Abstract: Artificial intelligence (AI) has disrupted modern workplaces like never before and has induced digital workstyles. These technological advancements are generating significant interest among HR leaders to embrace AI in human resource management (HRM). Researchers and practitioners are keen to investigate the adoption of AI in HRM and the resultant human–machine collaboration. This study investigates HRM specific factors that enable and inhibit the adoption of AI in extended HR ecosystems and adopts a qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…Specifically, in terms of functional barriers, Prakash and Das (2022) discovered that the perceived value barriers, usage complexity, and privacy disclosure risks of digital contact-tracking apps can increase the intentions to resist such devices. Singh and Pandey (2024) also indicated that inefficient collaboration with AI devices is also a critical barrier to their usage. Yun and Park (2022) , conversely, found that the reliability of chatbot service quality positively impacts users’ satisfaction and repurchase intention.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Specifically, in terms of functional barriers, Prakash and Das (2022) discovered that the perceived value barriers, usage complexity, and privacy disclosure risks of digital contact-tracking apps can increase the intentions to resist such devices. Singh and Pandey (2024) also indicated that inefficient collaboration with AI devices is also a critical barrier to their usage. Yun and Park (2022) , conversely, found that the reliability of chatbot service quality positively impacts users’ satisfaction and repurchase intention.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%